La eficiente y eficaz aplicación de los procedimientos de Contratación Pública en situación de emergencia por concepto de COVID 19 en la provincia de Chimborazo y su incidencia frente a las acciones de control - Pumagualli Llerena, María Fernanda (2023)
ABSTRAC In the present research work, through a doctrinal legal study, the applicability of public procurement procedures in emergency situations was analyzed from the declaration of a health emergency due to COVID 19, which has been developed under a bibliographic review within government ordinances, rules and regulations which are based on public procurement. For the development of the research, a descriptive and documentary research methodology was used, with a mixed approach and a deductive method, which were developed in order to collect information accurately and reliably to respond to the objectives set. Keywords: covid-19, contracting, standards, bibliographic review, legal, public contracting.